China's land market auctions: evidence of corruption?. (September 2013) - Cai, Hongbin; Henderson, J. Vernon; Zhang, Qinghua
<x xml:space="preserve">Abstract</x> In China, urban land is allocated by leasehold sales by local officials. Attempting to end widespread corruption, the government now requires sales to be conducted publicly, by either English or "two‐stage" auctions. However, corruption persists through the choice of auction format and preauction side deals between favored bidders and local officials. Two‐stage auctions have a first stage where favored developers signal that auctions are "taken, " deterring entry of other bidders. Empirics show that both sales prices and competition are significantly less for two‐stage than English auctions. Selection on unobserved property characteristics is positive: officials divert hotter properties to two‐stage auctions.